Development for Anticancer Therapy: Small-Molecule Inhibitors Targeting Protein Kinase B - Chen, Shi-feng; Chen, Jian-Zhong (Mini Reviews in Medicinal Chemistry, 2013)
Protein kinase B (PKB, also known as Akt) plays a critical role in the multiple cellular processes including glucose metabolism, cell growth, survival, apoptosis, transcription, and cell migration. Unregulated activation of protein kinase B is common in a significant fraction of human cancer, making enzyme an exciting new target for cancer therapy. A series of inhibitors with different mechanisms have been found, which is bound to be a positive impact on drug screening and cancer treatment. However, the development of inhibitors targeting PKB has been hampered by lacking of PKB-specific and isoform-specific inhibitors. This article describes the structure and functions of PKB as well as the recent advances in the development and biological evaluation of PKB's inhibitors. It was focused on the developments of selective small-molecule inhibitors with a well-defined, direct molecular interaction with protein kinase B, expecting to give information to design new inhibitors with high selectivity, bioavailability, and potency.
Keywords: Cancer